PECULIARITIES OF PROCESSES OF CARBIDE FORMATION AND DISTRIBUTION OF Cr, Mn AND Ni IN WHITE CAST IRONS - V. V. Netrebko (Литьë и металлургия, 2015)
During crystallization of castings from white cast iron, carbides Me3С, Me7С3, Me23С6 were formed depending on chromium and carbon content. Impeded chromium diffusion caused formation of thermodynamically unstable and non-uniform phases (carbides). During heat treatment process stable equilibrium phases were formed as a result of rearrangement of the carbides’ crystal lattice, replacement of iron, manganese, nickel and silicon atoms by chromium atoms. The allocated atoms concentrated, forming inclusions of austenite inside the carbides. Holding during 9 hours at 720 °С and annealing decreased the non-uniformity of chromium distribution in the metallic base of cast iron containing 11,5 % Cr, and increased it in the cast iron containing 21,5 % Cr. Holding during 4.5 hours at 1050 °С and normalization decreased the non-uniformity of chromium distribution in the metallic base of cast iron containing 21,5 % Cr, and increased it in cast iron containing 11,5 % Cr.